East Asian Lobelioideae and ancient divergence of a giant rosette Lobelia in Himalayan Bhutan. Issue 2 (3rd April 2016) - Chen, Ling-Yun; Wang, Qing-Feng; Renner, Susanne S.
Abstract: Lobelioideae comprise about 1200 species in 30 genera worldwide and include famous cases of parallel evolution in the "giant rosette" lobelias occurring in East Africa, Hawaii, and Bhutan. To date, no phylogeny has included the Himalayan giant lobelia, and its age and phylogenetic distance from the Hawaiian and African giant species (the latter in the same section as the Bhutan species) are therefore unknown. Asian Lobelioideae in general have received little attention, partly because of the difficult access to material. Here we use nuclear and plastid markers of Lobelioideae (with worldwide sampling) to test the monophyly of the section that includes most Asian lobelias, and we then use a reduced concatenated matrix to resolve the position of Lobelia nubigena from Bhutan and of the likewise cold‐adapted lowland species L. sessilifolia . Most sequences come from herbarium material. Lobelia nubigena diverged from its Asian lowland relatives 13.8 (12.6–15) million years ago (about the time of the Bhutan Himalaya orogeny), and in an unexpected twist, L. sessilifolia is the sister species to a huge clade (ca. 265 species) that comprises African, South American, Asian, and the entire Hawaiian Lobelioideae radiation. The African and Hawaiian high‐elevation lobelias in our sample are younger than L. nubigena, although the time when gigantism evolved in this species cannot be precisely inferred. Our results support the previously hypothesized Asian origin of (1) the Hawaiian Lobelioideae, (2) Southeast Asian islands lobelias, and (3) the African Lobelia‐Rynchopetalum group, which also reached South America.